Strategi Marketing Public Relations Auto2000 - Nurul Fadillah; Nani Nurani Muksin (Institut Nalanda, 2024)
The business competition in the current era of digitalization is increasingly fierce, so companies need to adapt and are required to have good and innovative strategies. This research aims to analyze and describe the sustainability of Marketing Public Relations strategies at Auto2000 PT. Astra International Tbk. The theory used in this study is the Marketing Public Relations theory proposed by Kotler & Armstrong, which includes 9 tools of Marketing Public Relations: Publications, Events, Identity Media, News, Speeches, Public Service Activities, Sponsorship, Press Relations, and Product and Brand Publicity. This study uses a qualitative descriptive method, which is a problem-solving procedure investigated by describing the state of the research object based on existing facts. The data collection method employed was through interviews. The Publications involved creating persuasive, informative, and educational content to attract customers using social media. The Events activities included organizing a series of events aimed at introducing new products and sustaining various campaigns to increase brand awareness. For Identity Media, Auto2000 emphasized the characteristics of the logo and the use of dominant colors for each published content. In the News activities, Auto2000 utilized the website and made efforts to obtain organic news from mass media. For Speeches, a company spokesperson was appointed to deliver credible information and clarify issues. The Public Service Activities involved social initiatives as a form of responsive services and social assistance. Sponsorships supported events relevant to the company. Press Relations efforts were made to build good relationships with the media. For Product and Brand Publicity, Auto2000 ensured the quality of services and products, complemented by high publicity.